Weather &Amp; Climate Services for the Energy Industry 2018
DOI: 10.1007/978-3-319-68418-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and Extended-Range Ensemble Weather Forecasting

Abstract: The chapter provides an overview of ensemble weather forecasting for the medium-and extended-range (days to weeks ahead). It reviews the methods used to account for uncertainties in the initial conditions and in the forecast models themselves. The chapter explores the challenges of making useful forecasts for the sub-seasonal timescale, beyond the typical limit for skilful day-to-day forecasts, and considers some of the sources of predictability such as the Madden-Julian oscillation (MJO) that make this possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…At these timescales the influence of initial atmospheric conditions, used to initialise the model, reduces and chaotic processes in the Earth system become more dominant. These timescales are considered the limit for day-to-day predictability [39]. Forecasts are also available for extended-and long-range (46 days and 3-7 months ahead, respectively) associated with longer-term predictability in the climate system.…”
Section: Model Forecasts and Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At these timescales the influence of initial atmospheric conditions, used to initialise the model, reduces and chaotic processes in the Earth system become more dominant. These timescales are considered the limit for day-to-day predictability [39]. Forecasts are also available for extended-and long-range (46 days and 3-7 months ahead, respectively) associated with longer-term predictability in the climate system.…”
Section: Model Forecasts and Projectionsmentioning
confidence: 99%
“…Subseasonal, seasonal to decadal forecasts make use of important long-term sources of predictability within the Earth system, e.g. the Madden-Julian Oscillation or El-Niño Southern Oscillation, which provide potential for forecasts from 1 month up to 1 decade ahead [39,[41][42][43]. Although these forecasts are generally more uncertain than weather forecasts, for biosecurity applications there are many opportunities to utilise these as input to pest, pathogen and disease EWSs [44], or for strategic agricultural decisions, e.g.…”
Section: Model Forecasts and Projectionsmentioning
confidence: 99%
“…Thus, the season-long outlooks might fail to capture the variances and occurrences of extreme events at daily time step [13,14], hugely limiting the applicability in crop growth models. The spatio-temporal uncertainties in the simulated weather parameters during season-long predictions can be reduced with medium-range forecasts [15]. Ortiz-Monasterio et al [3], after analysing winter wheat from 1985-1992 in the district of Punjab, India, suggested that high temperatures about and after the heading date (which occurred during the middle of February) had a detrimental effect on the crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…A deterministic forecast gives no indication of the forecast sensitivity to initial errors and approximations: How likely is a given forecast to be correct? Ensemble prediction is becoming increasingly important on all timescales from the short (one or three days ahead) to the seasonal range and beyond (Ancell, 2013; Richardson, 2018; Palmer, 2019). An ensemble prediction system (EPS) is an NWP system in which several predicted scenarios from the same model are used to represent the uncertainty in a weather forecast as well as the most likely outcome.…”
Section: Introductionmentioning
confidence: 99%